2022
DOI: 10.1093/ejcts/ezac355
|View full text |Cite
|
Sign up to set email alerts
|

The European Registry for Patients with Mechanical Circulatory Support (EUROMACS): third Paediatric (Paedi-EUROMACS) report

Abstract: OBJECTIVES A third paediatric report has been generated from the European Registry for Patients with Mechanical Circulatory Support (EUROMACS). The purpose of EUROMACS, which is operated by the European Association for Cardio-Thoracic Surgery, is to gather data related to durable mechanical circulatory support for scientific purposes and to publish reports with respect to the course of mechanical circulatory support therapy. Since the first report issued, efforts to increase compliance and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Only two patients were reported from the registry with ccTGA and overall 10 of 16 were either on support or transplanted at the time of the report. 11,12 Another case report by Tadokoro et al . 8 reported on two adult patients with ccTGA who underwent VAD implant and they employed both preoperative computed tomography (CT) and intraoperative TEE for guidance of inflow cannula placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two patients were reported from the registry with ccTGA and overall 10 of 16 were either on support or transplanted at the time of the report. 11,12 Another case report by Tadokoro et al . 8 reported on two adult patients with ccTGA who underwent VAD implant and they employed both preoperative computed tomography (CT) and intraoperative TEE for guidance of inflow cannula placement.…”
Section: Discussionmentioning
confidence: 99%
“…Only two patients were reported from the registry with ccTGA and overall 10 of 16 were either on support or transplanted at the time of the report. 11,12 Another case report by Tadokoro et al 8 reported on two adult patients with ccTGA who underwent VAD implant and they employed both preoperative computed tomography (CT) and intraoperative TEE for guidance of inflow cannula placement. A review by Riggs et al 13 outlines the representative case reports in largely adult patients with ccTGA requiring VAD (16/19), with the vast majority being successfully transplanted or still on support at the time of their report.…”
Section: Discussionmentioning
confidence: 99%
“…15 In children, one year after VAD implantation, almost 50% are transplanted and only 26% of children are still on VAD support. 14 This picture is totally different in adults with well over 50% still on device. 15 In this study the median support time in the ICD Group was even shorter, with just around 2 months compared to the control group with almost one year.…”
Section: Discussionmentioning
confidence: 99%
“…Children on VAD support do have shorter waiting times for cardiac transplantation and the number of children with permanent support is low. In the last pediatric EUROMACS report the percentage of children with the intention of destination therapy was lower than 1% 14 while this percentage in adults was over 20% 15 . In children, one year after VAD implantation, almost 50% are transplanted and only 26% of children are still on VAD support 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation